Answer:
Part A: [tex]t = v_0/a_0[/tex]
Part B: [tex]t = v_0/a_0[/tex]
Part C: [tex]v_0^2/a_0[/tex]
Explanation:
Part A:
We will use the following kinematics equation:
[tex]v = v_0 + at\\0 = v_0 - a_0t\\t = \frac{v_0}{a_0}[/tex]
Part B:
We will use the same kinematics equation:
[tex]v = v_0 + at\\v_0 = 0 + a_0t\\t = \frac{v_0}{a_0}[/tex]
Part C:
The total time takes is 2t.
So the train moves a distance of
[tex]x = v_0(2t) = 2v_0(\frac{v_0}{a_0}) = \frac{2v_0^2}{a_0}[/tex]
And the car moves a distance in Part A and in Part B:
[tex]d_A = v_0t + \frac{1}{2}at^2 = v_0(\frac{v_0}{a_0}) - \frac{1}{2}a_0(\frac{v_0^2}{a_0^2}) = \frac{v_0^2}{a_0} - \frac{v_0^2}{2a_0} = \frac{v_0^2}{2a_0}\\d_B = v_0t + \frac{1}{2}at^2 = 0 + \frac{1}{2}a_0(\frac{v_0^2}{a_0^2}) = \frac{v_0^2}{2a_0}[/tex]
So the total distance that the car traveled is [tex]d = \frac{v_0^2}{a_0}[/tex]
The difference between the train and the car is
[tex]x - d = \frac{2v_0^2}{a_0} - \frac{v_0^2}{a_0} = \frac{v_0^2}{a_0}[/tex]